Input and Output Condition And Water Storage District of Lake Buyan in Buleleng regency Sukasada - Dewa Made Atmaja (Media Komunikasi Geografi, 2016)
Research conducted at the District Sukasada Lake Buyan Buleleng, which aims to find the input conditions (precipitation, runoff) water lake Buyan over the last 10 years. Knowing the condition of outputs (evaporation, consumption, and savings) water of Lake Buyan period of 10 years. Knowing the Buyan lake water storage over the last 10 years between 1999 and 2008. The study design was a field survey includes observation, measurement, and laboratory analysis. Primary data and samples based on stratified random sampling for water consumption. Secondary data were obtained from the relevant agencies. The data obtained were processed with the formula of Theissen Polygons, Thornthwaite-Mather, Penman, Welch, and Seyhan. Furthermore, using qualitative descriptive analysis. The results showed the water input Buyan lake consists of: rainfall and runoff decline. Meanwhile, the output consists of free water evaporation, water consumption, savings and seepage out of the lake, three of these four variables must be increased. This was caused by the increase in population, the destruction of forests and climate change. So the water balance of the lake Buyan be disrupted  Keywords: Lake Buyan, Balance Water